From Moated Castle to Modern Parlour: Anna Letitia Barbauld’s Theorization of Wonder, Women, and the Novel - Ready, Kathryn (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2020)
As a literary critic Anna Letitia Barbauld provides important evidence for those who have sought to challenge a long-established critical view that the development of the novel was premised on a renunciation of the wonders of romance which went hand in hand with the project of Enlightenment science and its rejection of miracles and the supernatural. At the same time, she presents an alternative perspective from that of influential eighteenth-century male critics such as Samuel Johnson regarding the relationship between novels and romances, and a sharply contrasting view of the place of wonder within the overall history of fiction. Against male contemporaries, she makes a case for women’s continuing special claims as readers and writers of fiction based in part on their greater receptivity to emotions such as that of wonder, challenging Johnson’s implicit positioning of men as the leaders of a developing form of literary realism that required a broad knowledge of nature and society.